PTH-176 Audit to Evaluate the Gastroenterology Registrar of the Week Service in University Hospitals of Leicester. (4th June 2013) - Gordon, V M; Rogers, D; Hooper, P
Abstract : Introduction: The 'Registrar of the Week' service initially started in response to a Primary Care Trust initiative for Gastroenterology advice to GP's. This started as project 'Batphone'. The Gastroenterology department saw an ideal opportunity to start a Gastroenterology phone advice service which would be manned by an allocated Gastroenterology Registrar of the week, running Monday to Friday, 9–5pm excluding bank holidays. This started in August 2011. We give advice and see patients within the Leicester Royal Infirmary (LRI) as well as give advice to GP's and across site at the Leicster General Hospital (LGH) and Glenfield General Hospital (GGH). Methods: We collected data using a designed proforma to document all calls including origin, date time and also a summary sheet for the day. 262 days documentation was reviewed as these were complete. These were analysed. Results: The number of calls in 262 days was 2652. The range was 1- 36 calls per day, but on average 10 per day. 512 patients were identified for a Gastroenterology ward. There were 607 patients physically reviewed. 1870 calls came from the LRI, 165 from LGH, 195 from GGH and 276 GP calls. This works out roughly 1 call per day from each of the latter. Conclusion: We have seen a great increase in the usage of our service. We think that the audit data may well be an under reflection of the work done as people forget to fill the sheets in. The intensity is unpredictable. The number of GP calls is far lower than the number of hospital calls. It was felt overall the service was being avidly utilised by mainly medical and surgical teams and that it was also good experience for our Gastroenterology specialist Registrars. There were misuses of the telephone for example patients and relatives being put though. We are hoping to reduce this by education and circulation of further guidelines. The things we intend to change are the actual telephone as the reception is poor. Referrals that need to be seen the same day should be referred before 12pm. Guidelines for referral will be circulated. There will be more formalised consultant back-up in the future. We believe our service has been a success especially in the sense that we are able to know about and manage patients earlier although we think the efficiency of the service could be improved. We intend on re-auditing this service in the future so that we can continually improve it. Disclosure of Interest: None Declared.